2016
DOI: 10.1371/journal.pone.0164620
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual and Reproductive Factors and Risk of Gastric and Colorectal Cancer in Spain

Abstract: BackgroundSex hormones play a role in gastric cancer and colorectal cancer etiology, however, epidemiological evidence is inconsistent. This study examines the influence of menstrual and reproductive factors over the risk of both tumors.MethodsIn this case-control study 128 women with gastric cancer and 1293 controls, as well as 562 female and colorectal cancer cases and 1605 controls were recruited in 9 and 11 Spanish provinces, respectively. Population controls were frequency matched to cases by age and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…For the specific case of GC, MCC-Spain recruited 459 histologically confirmed cases and 3440 population controls between September 2008 and December 2013 in 10 of the 12 participating provinces (all except Gerona and Guipúzcoa). The detailed selection process of GC cases and controls has been previously described elsewhere [15,16]. Briefly, participants able to answer the questionnaire, who had lived in the study area for at least 6 months before the diagnosis, and were 20-85 years old were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…For the specific case of GC, MCC-Spain recruited 459 histologically confirmed cases and 3440 population controls between September 2008 and December 2013 in 10 of the 12 participating provinces (all except Gerona and Guipúzcoa). The detailed selection process of GC cases and controls has been previously described elsewhere [15,16]. Briefly, participants able to answer the questionnaire, who had lived in the study area for at least 6 months before the diagnosis, and were 20-85 years old were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of an Egyptian study from 2010 found that breastfeeding for 19 months and longer per live birth was associated with lower CRC risk (OR = 0.2, 95% CI = 0.1 to 0.4) ( 26 ). Other studies found no association ( 13 , 23 , 27 ). Only 1 previous study ( 23 ) provided stratified analysis by tumor location and found a lower risk with breastfeeding only for proximal colon cancer (HR = 0.65, 95% CI = 0.43 to 0.99) compared with null associations for distal colon and rectum cancer, which is in line with our results.…”
Section: Discussionmentioning
confidence: 75%
“…Other different approaches are needed in study design and statistical method. Several Western studies showed inconsistent results in the association between GC and MHT use [ 17 , 18 , 33 ]. As estrogen receptor positivity has been reported to be associated with poor outcome in GC patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%